Kingdom of Swaziland : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Kingdom of Swaziland. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Swaziland's growth has been recovering since the 2010-11 fiscal crisis, albeit at a slower pace recently. Growth recovery following the fiscal crisis was broadly supported by the manufacturing and service sectors. In 2015, however, growth is expected to slow, owing to adverse weather conditions and a slowdown in tourism and transport sectors. Swaziland's growth outlook is projected to remain subdued over the medium term, while it is clouded with downside risks. Growth is expected to slow in 2016/17, followed by a modest recovery in the following years.